Lack of Serologic Evidence of Infection Among Health Care Personnel and Other Contacts of First 2 Confirmed Patients With COVID-19 in Illinois, 2020. (January 2021) - McPherson, Tristan D.; Ghinai, Isaac; Binder, Alison M.; Freeman, Brandi D.; Hoskin Snelling, Chantel; Hunter, Jennifer C.; Anderson, Kristin M.; Davenport, Polly; Rudd, Deborah L.; Zafer, Mujeeb; Christiansen, Demian; Joshi, Kiran; et al.
Objectives: Widespread global transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus causing coronavirus disease 2019 (COVID-19), continues. Many questions remain about asymptomatic or atypical infections and transmission dynamics. We used comprehensive contact tracing of the first 2 confirmed patients in Illinois with COVID-19 and serologic SARS-CoV-2 antibody testing to determine whether contacts had evidence of undetected COVID-19. Methods: Contacts were eligible for serologic follow-up if previously tested for COVID-19 during an initial investigation or had greater-risk exposures. Contacts completed a standardized questionnaire during the initial investigation. We classified exposure risk as high, medium, or low based on interactions with 2 index patients and use of personal protective equipment (PPE). Serologic testing used a SARS-CoV-2 spike enzyme-linked immunosorbent assay on serum specimens collected from participants approximately 6 weeks after initial exposure to either index patient. The 2 index patients provided serum specimens throughout their illness. We collected data on demographic, exposure, and epidemiologic characteristics. Results: Of 347 contacts, 110 were eligible for serologic follow-up; 59 (17% of all contacts) enrolled. Of these, 53 (90%) were health care personnel and 6 (10%) were community contacts. Seventeen (29%) reported high-risk exposures, 15 (25%) medium-risk, and 27 (46%) low-risk. No participant had evidence of SARS-CoV-2 antibodies. The 2 index patients had antibodies detected at dilutions >1:6400 within 4 weeks after symptom onset. Conclusions: In serologic follow-up of the first 2 known patients in Illinois with COVID-19, we found no secondary transmission among tested contacts. Lack of seroconversion among these contacts adds to our understanding of conditions (ie, use of PPE) under which SARS-CoV-2 infections might not result in transmission and demonstrates that SARS-CoV-2 antibody testing is a useful tool to verify epidemiologic findings.